The Islamization in Bugis Society during the Darul Islam Era under Kahar Muzakar in 1960s - Andini, Batari Oja (IAIN Surakarta, 2017)
This paper describes one of the reasons why Islam is so embedded in the identity and the culture of Bugis society. By studying some works of literature about Darul Islam in South Sulawesi and the Bugis pre-Islamic religion, the Islamization process in South Sulawesi was colored by fears, terror, and massacre. It was in Darul Islam Era, under Kahar Muzakar, when Bugis pre-Islamic religion was brutally replaced by Islam since the gerombolan wanted to establish Indonesia Islamic State (NII). This paper also offers a description of Indonesian politics in micro view, the local history of the politics in South Sulawesi.Â Keywords:Islamization, Darul Islam, Bugis, and Kahar Muzakar